Black carbon mixing state impacts on cloud microphysical properties: Effects of aerosol plume and environmental conditions. Issue 10 (31st May 2016) - Ching, J.; Riemer, N.; West, M.
Abstract: Black carbon (BC) is usually mixed with other aerosol species within individual aerosol particles. This mixture, along with the particles' size and morphology, determines the particles' optical and cloud condensation nuclei properties, and hence black carbon's climate impacts. In this study, the particle‐resolved aerosol model PartMC‐MOSAIC (Particle Monte Carlo‐Model for Simulating Aerosol Interactions and Chemistry) was used to quantify the importance of black carbon mixing state for predicting cloud microphysical quantities. Based on a set of about 100 cloud parcel simulations a process‐level analysis framework was developed to attribute the response in cloud microphysical properties to changes in the underlying aerosol population ("plume effect") and the cloud parcel cooling rate ("parcel effect"). In most of the simulations the plume and parcel effects had opposite signs, with the plume effect dominating. The response of cloud droplet number concentration to changes in BC emissions depended on the BC mixing state. When the aerosol population contained mainly aged BC, an increase in BC emission increased cloud droplet number concentrations ("additive effect"). In contrast, when the aerosol population contained mainly fresh BC particles, they act as sinks for condensable gaseous species, resulting in decreasing cloud droplet number concentration as BC emissions were increased ("competition effect"). Additionally, we quantified the error in cloud microphysical quantities when neglecting the information on BC mixing state. The errors ranged from −12% to +45% for the cloud droplet number fraction, from 0% to +1022% for the nucleation‐scavenged BC mass fraction, from −12% to +4% for the effective radius, and from −30% to +60% for the relative dispersion. Key Points: Particle‐resolved cloud parcel simulations resolving aerosol mixing state are performed Importance of black carbon particles mixing state is examined for various environmental conditions Errors in predicting cloud microphysical properties without resolving mixing state are reported